2014
DOI: 10.1088/1468-6996/15/2/025004
|View full text |Cite
|
Sign up to set email alerts
|

Laser-vibrometric ultrasonic characterization of resonant modes and quality factors of Ge membranes

Abstract: The vibrations of a single-crystal germanium (Ge) membrane are studied in air and vacuum using laser vibrometry, in order to determine mechanical properties such as Q-factors, tensile stress, anisotropy, and robustness to shock. Resonance modes up to 3:2 are identified, giving a residual stress measurement of 0.22 GPa, consistent with the value obtained from x-ray relaxation studies. The membrane is found to be isotropic, with Q-factors ranging from around 40 at atmospheric pressure to over 3200 at mbar, sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Previous research has confirmed that the membranes resonate in the stress-governed regime [5]. The stress can be measured by performing a sweep of frequency and identifying resonances from the increased vibrational amplitudes.…”
Section: Theoretical Backgroundmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous research has confirmed that the membranes resonate in the stress-governed regime [5]. The stress can be measured by performing a sweep of frequency and identifying resonances from the increased vibrational amplitudes.…”
Section: Theoretical Backgroundmentioning
confidence: 94%
“…A pair of linear stages were used to produce a two-dimensional scanning system, onto which the IOS laser head was mounted. Frequency scans at fixed positions were used to find resonant frequencies, at positions chosen in regions where high displacements are expected for certain modes, for example at the centre and along the diagonal of the membrane [5]. Following this, positional scans were performed using a raster-scan pattern at fixed frequencies to identify the modes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations